P096 Which patients with known Crohn's disease after an ileo-colonoscopy will benefit most from small bowel capsule endoscopy?. (27th May 2021) - Viazis, N; Mountaki, A; Koustenis, K; Veretanos, C; Arvanitis, K; Georgiadi, T; Karampekos, G; Manolakis, A; Archavlis, E; Christidou, A; Mela, M; Mantzaris, G
Abstract: Background: Ileo-colonoscopy with biopsies is considered the gold standard for the diagnosis and management of Crohn's disease (CD). In contrast, the role of small bowel capsule endoscopy (SBCE) is limited currently in cases where ileo-colonoscopy and imaging techniques raise doubts on the diagnosis or cannot explain certain clinical manifestations of Crohn's disease. The aim of our study was to determine whether there are patients with endoscopically confirmed established CD who could get additional benefit by SBCE. Methods: Retrospective analysis of prospectively collected data from 6301 patients subjected to SBCE in our department from 1 st March 2003 to 18 th February 2021. Patients with CD diagnosed by ileo-colonoscopy or total colonoscopy only (because the ileo-caecal valve could not be intubated) prior to SBCE were included in the study and biopsies. SBCE had been performed only in patients who lacked any clinical and/or imaging (CT/MRE) evidence of bowel obstruction. The presence and extent of mucosal lesions, namely local and/or diffuse erythema, erosions and ulcers (aphthous, superficial and/or deep) throughout the small intestine, which may be difficult to identify by traditional imaging, could either explain clinical manifestations unrelated to the findings of colonoscopy or led onto reassessment of applied treatments were sought by SBCE. Results: The study sample consisted of 1002 patients (males/females: 511/491, mean age ± SD: 52.6±27.3). Among these, CD had been diagnosed with colonoscopy (and not ileo-colonoscopy) in 293 (29.2%) subjects and small bowel involvement was seen in 104 (35.5%) patients. The vast majority of these patients had lesions only in the terminal ileum (n=81, 77.8%), while the remaining patients (n=23, 22.2%) had additional lesions in more proximal parts of the small bowel. Among the 709 (70.8%) patients in whom CD had been diagnosed by ileo-colonoscopy, lesions in the terminal ileum were found in 407 (57.4 %) patients; SBCE revealed more proximal lesions in 104 patients (25.5%). In the remaining 307 patients (43.3%) in whom ileo-colonoscopy did not reveal terminal ileum involvement, more proximal small bowel lesions were seen in 35 (11.4%) patients. These lesions were mainly apthoid ulcers or larger ulcers, findings that led to a change in therapeutic management in 17 patients (48.6%). Conclusion: SBCE identifies more proximal small bowel lesions in a substantial number of patients with CD established by traditional endoscopic techniques. When these lesions are more severe and extensive they may lead onto re-evaluation of the personalized therapeutic strategies.